Phylogeny and systematics of the fern genus Pellaea and its allies (Pteridaceae) - Zhao, Jing; Ma, Dan-Ni; Smith, Alan R.; Liang, Zhen-Long; Zhou, Xin-Mao; Zhang, Li-Bing (Phytotaxa, 2025)
The pellaeid ferns constitute a monophyletic, xeric-adapted lineage in the large fern family Pteridaceae. Previous studies, with relatively small taxon and character sampling, resolved the major relationships in the pellaeid ferns and found the most species-rich genus, Pellaea, to be polyphyletic. In this study, DNA sequences of nine plastid markers of 149 accessions of the pellaeids representing ca. 61 (73% of total) species and 71 accessions representing ca. 40 species of Myriopteris were used to reconstruct a new phylogeny. All major relationships in the pellaeids are well resolved and strongly supported. Pellaea is confirmed to be polyphyletic. Based on their phylogeny, morphology, and distribution, we propose to recognize eight genera, all now monophyletic, in the pellaeids. These new and revised circumscriptions result in a monophyletic Pellaea s. str.; they also include one resurrected and recircumscribed genus, Paraceterach, and two small new genera, Kirkpatrickia and Windhamia, with one and three species, respectively.